The profile of nursing professors/teaching nurse in "stricto sensu" postgraduation programs of public institutions - Susan Bublitz; Carmem Lúcia Colomé Beck; Rosângela Marion da Silva; Isabel Cristina Saboia Sturbelle (Universidade Federal de Santa Maria, 2019)
Aim: to identify the sociodemographic and occupational profile of teaching nurses working in stricto sensu postgraduate programs in Nursing of public institutions in Rio Grande do Sul. Method: quantitative, descriptive and exploratory study, developed with teaching nurses from three federal univers ities. The data collection was from November 2015 to October 2016, through a sociodemographic and labor questionnaire. The results were analyzed by the Statistical Analysis System software. Results: there was predominance of females, mean age of 53.92 and married / stable union. They entered graduate school between 2009 and 2014, have masters and doctorate students, have no other job, have not been away from work for more than three days, as well as in the last six months. Conclusion: the results have important characteristics on the profile of teaching nu